GLOBALISATION, SUSTAINABILITY AND THE NEW AGRARIAN REGIONS: FOOD, LABOUR AND ENVIRONMENTAL VALUES - Marsden, Terry K.; Cavalcanti, Josefa Salete Barbosa (Cadernos de Ciência & Tecnologia, 2001)
A globalização da agricultura e dos alimentos ocorre juntamente com processos de homogeneização e diferenciação, oferecendo as bases para a implementação de regulações e contestações que emergem dos modos como os atores sociais lidam com as interpretações e gradações dos alimentos, trabalho e meio ambiente. É, portanto, nessa arena política que as mudanças sociais e a sustentabilidade dos novos espaços agrários devem ser compreendidas. O artigo, com referência empírica aos novos distritos agrários do Nordeste brasileiro, examina as transformações em curso, no que se refere às mudanças nos mercados, estruturas de produção e práticas de trabalho; demonstra como há uma dinâmica principal, criando e remodelando esses espaços, associada com valores assimétricos baseados nas definições de qualidades e parâmetros externos dos alimentos, em comparação com aqueles associados com a qualidade do trabalho e dos ambientes "naturais", nos quais os alimentos crescem. Os processos em curso estão fortemente questionando a sustentabilidade desses desenvolvimentos. Conclui que a produção superintensiva não pode mais se apoiar em bases tecnológicas tais como aquelas associadas à irrigação e gerência da água - para reduzir a acumulação dos riscos sociais e ambientais no sistema de produção e oferta dos alimentos. GLOBALISATION, SUSTAINABILITY AND THE NEW AGRARIAN REGIONS: FOOD, LABOUR AND ENVIRONMENTAL VALUES ABSTRACT The globalisation of agriculture and food develops alongside contradictory processes of homogenisation and differentiation, providing grounds for enforcement of regulations and contestations that emerge from the ways in which social actors deal with interpretations and gradations of food, labour and the environment. It is therefore within this political arena that social changes and sustainability of the new agrarian sites have to be accounted for. The paper, with empirical reference to the new agrarian districts of Northeast Brazil, examines the social transformations occurring regarding changes in markets, production structures and labour practices; it shows how there is a major dynamics creating and reshaping such production spaces which is associated with the asymmetrical value placed upon the externalised quality definitions and parameters of the foods, compared with those associated with the quality of labour or the natural environments in which the foods are grown. The processes underway are severely questioning the sustainability of such developments. Super-intensive production, it is concluded, can no longer rely upon technological fixes-such as those associated with irrigation and water management- to halt the accumulation of both environmental or social risks in the production and supply system.